COLLECTIVE SECURITY AND THE TWIN PRINCIPLES OF THE RESPONSIBILITY TO PROTECT & THE DUTY TO PREVENT. A CASE STUDY OF THE YUGOSLAV & SOMALI CRISES - Ebaye, Sunday Esoso Nsed (IJRDO Journal of International affairs and Global strategy, 2020)
To propagate the UN philosophy of collective-security as a system of cooperation among states such that an act of aggression against one of its members is an act of aggression against all of its members, meaning the safety of all by all, the United-Nations-High-Level-Panel suggests collective-security should rest on three pillars: the continued need for collective-responses at the global, regional and national levels, the acceptance that certain threats pose serious security concerns to all states, and the Responsibility to Protect, in the realization that some states cannot and will not protect their own people and will harm their neighbours. A fourth pillar; the Duty to Prevent, which focuses attention on the threat posed by weapons-of-mass-destructions, rogue states and terrorism and the need for collective military intervention has also been added. However, there is a danger in adding these new principles to the UN-collective-security-system already plagued by radical defects. Wouldn’t these new pillars – Responsibility to Protect and Duty to Prevent - result in international insecurity? The premise of this research is the conviction that the UN is capable of dealing with the main geo-political problems- the creation of a secured world, and is, in fact indispensable to that end. Using the Yugoslav and Somali experiences as case studies, the intent therefore is to explore the collective-security-mechanism as envisioned by the UN-Charter and the incorporation of the Responsibility-to-Protect, and the Duty-to-Prevent. The data were collected through content analysis and analysed using the quantitative chi-square scientific method. Findings revealed that there is no significant difference between the UN collective security/twin principles of the responsibility to protect & the duty to prevent and the vested interest of the U.S in the management of the Yugoslav and Somali crises. The UN consciously or unconsciously allowed itself to be manipulated by a world power- the U.S, seeking universal hegemony. The research recommends a review of the present five-permanent-membership structure of the UNSC to include at least one powerful State from each continent. The membership of the UNSC should be restructured to include three major-countries from each continent, each representing their sub-regions aimed at making the system more balanced. Adoption of a wider scope of the concept of aggression to include indirect aggression in the form of sabotages, economic-aggression, and other forms of pressure, initiated by the powerful states, aimed at bringing the weaker states under the subjugation of the world powers. Review of the UN-charter to give an explicit definition of what constitutes threat to international peace and security. Arms control/regulation, as the ‘Big-Five’/economically powerful states are still investing more in developing deadly weapons-of-mass-destruction. A new international treaty making it a crime to test weapons of mass destruction should be concluded by the UN. The UN must therefore act; as envisaged in the Charter, as the guardian of the security of nations, especially the small countries, and as a catalyst for promotion of the primacy of the rule of law in international relations.